Risk factors for lower extremity injury: a review of the literature. Issue 1 (1st February 2003) - Murphy, D F; Connolly, D A J; Beynnon, B D
Abstract : Prospective studies on risk factors for lower extremity injury are reviewed. Many intrinsic and extrinsic risk factors have been implicated; however, there is little agreement with respect to the findings. Future prospective studies are needed using sufficient sample sizes of males and females, including collection of exposure data, and using established methods for identifying and classifying injury severity to conclusively determine addtional risk factors for lower extremity injury.